XOTIN-QIZLARDA PROFESSIONAL-XIZMAT KARYERASINI RIVOJLANTIRIShNING IJTIMOIY-PSIXOLOGIK DETERMIMANTLARI - Toxirova, G.D. (SCIENCE and SOCIETY, 2025)
The article, Career success, career, promotion. In other words, it is the result of a person's specific behavior and attitude in work related to professional growth, and explains its structure. An individual career is a sequence of individual development of behavior patterns and work experience, both conscious and independent, to move up the career ladder. It also embodies the stages of a person's professional life and individuality in entrepreneurial activity.
Keywords: professional career; individual professional career; professional self-sufficiency; authoritative decision